Antioxidant and Antimicrobial Potential of Wild Chestnut Ohrid Diamond Extract—An Opportunity for Creation of New Natural Products - Monika Stojanova; Dragutin Đukić; Marina Todor Stojanova; Aziz Şatana; Blazo Lalevic (Erwerbs-Obstbau, Springer, 2022)
The aim of this research was to prepare aqueous and ethanolic extracts of the seed and leaf of the wild chestnut known as Ohrid diamond and to determine the antioxidant and antimicrobial activity. In general, ethanolic extracts showed higher antioxidant potential compared with the aqueous extracts. Moreover, ethanolic seed extracts had better results in all of the antioxidant tests compared with the ethanolic extracts from the leaves. The ethanolic seed extract was characterized by a statistically significant (p < 0.05) lower IC50 value for the ability to capture DPPH radicals (0.63 mg/ml) compared with all other tested extracts. Furthermore, the extracts showed statistically significantly (p < 0.05) higher antimicrobial activity against five tested bacteria (Staphylococcus aureusATCC25923, Listeria monocytogenesATCC19115, Escherichia coliATCC11230, Shigella sonneiATCC29930, Pseudomonas aeruginosaATCC35554) compared to tetracycline and chloramphenicol. Given the good biological activity that was established, this research can serve as a novel starting point to contribute to greater utilization of this plant in the pharmaceutical, cosmetic, and food industries, and the obtained extracts could substitute for the numerous synthetic additives that are regularly used in these industries.